Estimation of Los Angeles and Micro Deval abrasion values for gneiss and granite using ANFIS approach - Pachoukova, Irina (Array, 2020)
Gneisses and granites mechanical properties knowledge such as the Los Angeles and Micro-Deval coefficients is very important for the engineer when designing and building civil engineering works. Laboratories test often performed to obtain Los Angeles and Micro-Deval values are expensive and time consuming. For this, the depths (parallel and perpendicular to the foliation planes) obtained during a rock drilling test will be used to estimate its coefficients Los Angeles and Micro-Deval. In this study, an ANFIS approach is used to estimate gneisses and granites Los Angeles and Micro-Deval that have been compared to the Multiple Linear Regression method. For this purpose, we have used a database of a sample size of 80 to determine the parameters of the ANFIS and Multiple Linear Regression models, and a second sample of size 15 used for the validation tests. The results obtained show us that we can estimate the mechanical properties (Los Angeles and Micro-Deval) of gneisses and granites with ANFIS approach.